Entrepreneurial intention from the context of B40 strata / Faizah Mashahadi, Syed Ashrene Syed Omar and Razmah Mahmod - Mashahadi, Faizah; Syed Omar, Syed Ashrene; Mahmod, Razmah (Universiti Teknologi MARA, 2021)
Malaysia has achieved much in reducing poverty and quality of life for most of the population. The government is consistently taking effective measures to transform the country from a low-income to high-income country. However, Malaysia is now facing with the reality of slow progression in the transformation process because of Covid-19. Indeed, the number of B40 strata has increased tremendously. Despite the pandemic that has forced the government to make major adjustment on the transformation program, the government is still optimist and committed to boost up the household income of low-income earners (B40). Due to the significance of entrepreneurship to improve standard of living and income distribution, this study aims to examine the determinants of entrepreneurial intention among B40 strata in Malaysia. Following the Theory of Planned Behaviour (TPB), the study examines the extent to which attitude, subjective norms, and perceived behavioral control predict entrepreneurial intention among B40 strata in Malaysia. A questionnaire survey is done using the sample of B40. The hypotheses are analysed by using partial least square-structural equation modeling (PLS-SEM). The result suggests that only attitude and perceived behavioural control are significant to explain B40 entrepreneurial intention. While subjective norm is found as a non-significant predictor in explaining B40 entrepreneurial intention. The paper extends the current knowledge on entrepreneurial intention by analysing TPB and provide insightful input from the context of entrepreneurial intention among B40 in Malaysia.